The features of the technical prose of the Kurdish Author Masoud Mohammad Jalizadah (A Case Study of his letter in lamenting Alaaddin Sajjadi) - هادي رضوان (QALAAI ZANIST SCIENTIFIC JOURNAL, 2019)
In the late nineteenth and early twentieth centuries, various Arabic prose schools were formed. Thes e schools includes the imitators, the inventors, and the moderates and extremists in modernism, which intense scientific and literary conflicts could be seen between them. The Non-Arabic Arabic writers have each been influenced by some of the Arabic literary schools. Massoud Muhammed Jalizadah is one of the great figures who lived until the end of the 20th century and died in 2002. Massoud Muhammed is considered among the Kurdish thinkers, intellectuals and literates who have left valuable works in both Kurdish and Arabic. Among these are a letter in lamenting Alaaddin Sajjadi, which indicates the author’s exemplary literary taste. In this letter, he is sometimes nearly a conservative imitator showing signs of mannerism and ambiguity in his prose; however, it does not lose its vitality and beauty. The author in this article examines the technical elements contained in this letter and talks about t he thoughts, the style of linguistic aesthetics and the emotions in it, and examines the various figures of speech used in it. Being influenced by both the old-fashioned and the contemporary, the boisterous and honest emotions and the signs of Kurdish culture are among the characteristics of Mas s oud Muhammed’s prose in this letter.